2015
DOI: 10.1177/1090198115571364
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behavior to Understand Cervical Cancer Screening Among Latinas

Abstract: To reduce the high incidence of cervical cancer among Latinas in the United States it is important to understand factors that predict screening behavior. The aim of this study was to test the utility of theory of planned behavior (TPB) in predicting cervical cancer screening among a group of Latinas. A sample of Latinas (N= 614) completed a baseline survey about Pap test attitudes subjective norms, perceived behavioral control, and intention to be screened for cervical cancer. At six-months cervical cancer scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 29 publications
13
73
4
Order By: Relevance
“…In Ethiopia; the highest prediction was observed in a study done to predict the intended use of condom in a rural population [16]. To this end; despite it is consistent with finding from few previous studies [15,19,17]; the current study revealed considerably low prediction of behavioral intention with only 23.5% of the variance in intention. Debatably; the TPB has been criticized for its insufficiency to effectively predict intention or behavior as it doesn't take into account the influence of emotional dimension in individuals' decision making process.…”
Section: Pearson's Correlations R Between Intention and Direct Measusupporting
confidence: 88%
See 1 more Smart Citation
“…In Ethiopia; the highest prediction was observed in a study done to predict the intended use of condom in a rural population [16]. To this end; despite it is consistent with finding from few previous studies [15,19,17]; the current study revealed considerably low prediction of behavioral intention with only 23.5% of the variance in intention. Debatably; the TPB has been criticized for its insufficiency to effectively predict intention or behavior as it doesn't take into account the influence of emotional dimension in individuals' decision making process.…”
Section: Pearson's Correlations R Between Intention and Direct Measusupporting
confidence: 88%
“…Importantly; TPB has been found to be effective in predicting the intended cancer screening behaviors such screening for breast and colorectal cancers. More specifically; the theory has produced an effective prediction of cervical cancer screening (CCS) behavioral intention with variances ranging from 27.6%-51% in different previous studies [18,19].…”
Section: Development Of Explicit Interventions To Changing Behaviors mentioning
confidence: 99%
“…One of the most popular theories for predicting health behaviours is the Theory of Planned Behavior (TPB). The utility of the TPB has been supported in a wide range of behaviours, such as smoking habits, alcohol drinking and tobacco use, health screening, toothbrushing, flossing and dental check‐ups. According to Ajzen, the TPB presupposes that intention influences behaviour, which is affected by the attitude towards behaviour (AT), subjective norms (SN), and perceived behavioural control (PBC).…”
Section: Introductionmentioning
confidence: 99%
“…The TPB has been widely applied into a variety of health behaviours, such as condom use (Molla, Astrom, & Berhane, ), physical activity (Hagger et al, ; Hagger, Chatzisarantis, & Biddle, ), cervical cancer screening (Roncancio et al, ), adherence to medication treatment (Rich, Brandes, Mullan, & Hagger, ), smoking (Alanazi, Lee, Dos Santos, Job, & Bahjri, ), use of social networking websites (Pelling & White, ), intention to use HIV counselling and testing (Abamecha, Godesso, & Girma, ; Kakoko, Åstrøm, Lugoe, & Lie, ), adherence to HIV medication (Vissman et al, ), and help‐seeking behaviours for mental health problems (Mo & Mak, ). A meta‐analysis of the TPB (Armitage & Conner, ) further supported the effectiveness of the theory, which accounted for 39% and 27% of the variance in intention and behaviour, respectively.…”
Section: Introductionmentioning
confidence: 99%